Grapes syn på samerna : En studie av en prästs syn på samernas religiositet vid sekelskiftet 1800 - Bredgaard, Linus (Linnéuniversitetet, Institutionen för kulturvetenskaper (KV), 2020)
This essay examines how a priest named Erik Grape stationed in Torne Lappmark at the turn of the nineteenth century looked at the Sami people, their religious life and religious practice. It also investigates how Grape looked at Christianity teaching, but also why in his texts he makes a clear opposition between Sami and Finns. Using Bruce Lincoln's theories in Holy terror the essay concluded that Grape sees the Sami as less Christian than the remaining population of the country. that he divides the Sami and Finns to strengthen the collective community by putting "we" vs. "them" groups against each other.